Severance Payments for Dismissed Employees in Germany - Christian Grund (Institute for the Study of Labor (IZA), 2003)
This contribution investigates severance payments for dismissed employees in Germany. Subsequent to an overview about the legal framework, we respond to the following questions: Who receives severance payments? By which characteristics is the level of severance payments determined? Is overcompensation to be considered a relevant issue? Hereby, individual and collective dismissals are always distinguished. This is the first study on this issue using individual representative data – the German Socio-Economic Panel – and multivariate methods. The results indicate that rather women, persons with many years of tenure and working in big firms receive severance payments. There is a huge variance in the size of the payments, which can only partly be explained by tenure, the wage, firm size and the region. At least one quarter of dismissed employees is better off in their following careers independent of having received a severance payment.
Keywords: M51; J53; J32; M52; 330; severance payments; dismissals; plant closings; Abfindung; Kündigung; Humankapital; Betriebszugehörigkeit; Schätzung; Deutschland